Characteristics of Syrian Villages in Linguistic Geography (Damascus University Journal of arts and humanities sciences, 2021)
The study of place names TOPONYMS receives a great attention and interest by researchers in linguistic geography, because from the perspective of the geographical researcher it reflects the role of the natural environment in the spatial distribution of rural communities, and it highlights the social and cultural heritage that characterizes the inhabitants, which is considered by some as part of the cultural and urban civilization. It is important to clarify these aspects at the level of the Syrian countryside, based on the descriptive، analytical, statistical approach and regional approach, through which individual regions have been classified and distinguished (nominally، linguistic regions), with similar names for villages (Dwir, Khrab,Rasm). The boundaries of some of these regions are somewhat are aligned to the administrative divisions of the governorates such as (Siha, Beit,..) and those of other regions correspond to the boundaries of certain climatic regions, as shown in the study, such as (Nabea, Ein). This latter pattern entails a set of names or vocabulary that are not beyond 2% of the names or words used for the total number of rural communities , villages or towns in the entire country. It is concluded from this study that the names given to the human centers or complexes remain ingrained in the minds of the inhabitants, and most of which appear in a complex form: with first name keeping the old word, and the subsequent word or second name using a modern one, sometimes with two contradictory meanings. At the same time, the names of the villages are distributed in the spatial and longitudinal pattern in most regions of the country.
Keywords: Characteristics of Syrian Villages in Linguistic Geography